Comparing the clinical outcomes in patients with atrial fibrillation receiving dual antiplatelet therapy and patients receiving an addition of an anticoagulant after coronary stent implantation: A systematic review and meta-analysis of observational studies. Issue 50 (December 2016) - Chaudhary, Nabin; Bundhun, Pravesh Kumar; Yan, He
Abstract: Background: Data regarding the clinical outcomes in patients with atrial fibrillation (AF) receiving dual antiplatelet therapy (DAPT) and an anticoagulant in addition to DAPT (DAPT + vitamin K antagonist [VKA]) after coronary stent implantation are still controversial. Therefore, in order to solve this issue, we aim to compare the adverse clinical outcomes in AF patients receiving DAPT and DAPT + VKA after percutaneous coronary intervention and stenting (PCI-S). Methods: Observational studies comparing the adverse clinical outcomes such as major bleeding, major adverse cardiovascular events, stroke, myocardial infarction, all-cause mortality, and stent thrombosis (ST) in AF patients receiving DAPT + VKA therapy, and DAPT after PCI-S have been searched from Medline, EMBASE, and PubMed databases. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to express the pooled effect on discontinuous variables, and the pooled analyses were performed with RevMan 5.3. Results: Eighteen studies consisting of a total of 20, 456 patients with AF (7203 patients received DAPT + VKA and 13, 253 patients received DAPT after PCI-S) were included in this meta-analysis. At a mean follow-up period of 15 months, the risk of major bleeding was significantly higher in DAPT + VKA group, with OR 0.62 (95% CI 0.50–0.77, P  < 0.0001). There was no significant differences in myocardial infarction and major adverse cardiovascular event between DAPT + VKA and DAPT, with OR 1.27 (95% CI 0.92–1.77, P  = 0.15) and OR 1.17 (95% CI 0.99–1.39, P  = 0.07), respectively. However, the ST, stroke, and all-cause mortality were significantly lower in the DAPT + VKA group, with OR 1.98 (95% CI 1.03–3.81, P  = 0.04), 1.59 (95% CI 1.08–2.34, P  = 0.02), and 1.41 (95% CI 1.03–1.94, P  = 0.03), respectively. Conclusion: At a mean follow-up period of 15 months, DAPT + VKA was associated with significantly lower risk of stroke, ST, and all-cause mortality in AF patients after PCI-S compared with DAPT group. However, the risk of major bleeding was significantly higher in the DAPT + VKA group.